2008
DOI: 10.1016/j.limno.2007.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Macrozoobenthic community of Fuxian Lake, the deepest lake of southwest China

Abstract: Located in the Yunnan-Guizhou Plateau in southwest China, Fuxian Lake covers an area of 211 km 2 , with maximum depth of 155 m. It is known to have a unique fauna, including 14 described endemic species. In order to describe the zoobenthic community of the lake more completely, the present study was conducted from August 2002 to August 2003. Altogether 62 benthic taxa, including 22 oligochaetes, 21 molluscs and 18 insects were identified, of which the dominant taxa belonged to Potamothrix, Procladius and Parap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Erhai Lake (EL) has undergone alteration from mesotrophic to eutrophic conditions owing to excessive usage of chemical fertilizers and severe destruction of wetland vegetation along the lakeshore (Hu et al, 2014; Wang et al, 2015a). Fuxian Lake (FXL) is oligo-mesotrophic (Cui et al, 2008). Lugu Lake (LGL) is oligotrophic, and clear with abundant submerged plants (Liao et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Erhai Lake (EL) has undergone alteration from mesotrophic to eutrophic conditions owing to excessive usage of chemical fertilizers and severe destruction of wetland vegetation along the lakeshore (Hu et al, 2014; Wang et al, 2015a). Fuxian Lake (FXL) is oligo-mesotrophic (Cui et al, 2008). Lugu Lake (LGL) is oligotrophic, and clear with abundant submerged plants (Liao et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Amnicola limosa had a significant positive correlation with coliforms in Lake Rippowam. Positive associations between coliforms and snails were found in other studies (Giovanelli et al 2005;Cui et al 2008). Studies that focused on water bodies heavily contaminated with sewage effluent often reported that only certain species of snails -usually from the very tolerant family Physidae -were plentiful in areas with high coliform counts (Cui et al 2008;Varnosfaderany et al 2010).…”
Section: Resultsmentioning
confidence: 72%
“…Positive associations between coliforms and snails were found in other studies (Giovanelli et al 2005;Cui et al 2008). Studies that focused on water bodies heavily contaminated with sewage effluent often reported that only certain species of snails -usually from the very tolerant family Physidae -were plentiful in areas with high coliform counts (Cui et al 2008;Varnosfaderany et al 2010). Anoxic conditions resulting from nitrate influx, algal blooms, and subsequent bacterial population explosions make such habitats inhospitable to the gilled snails and other more sensitive Pulmonate species.…”
Section: Resultsmentioning
confidence: 82%
“…Both species exhibit differences in their radular morphology, which may indicate differences in their trophic specialization. This specialization may relate to the different environmental conditions in lakes: Lake Fuxian is a typical oligotrophic lake with far less biomass of benthic algae (plus different species of algae) than the eutrophic lakes Lake Xingyun and Qilu (CAS, 1989; Cui, Liu & Wang, ). Thus although allopatric separation has been the main driver of speciation, lineage differentiation may have been accelerated by diversifying selection in two rather different environments.…”
Section: Discussionmentioning
confidence: 99%